Hyperbaric Oxygen in Lower Limb Trauma (HOLLT); protocol for a randomised controlled trial. Issue 6 (11th June 2015) - Millar, Ian L; McGinnes, Rosemary A; Williamson, Owen; Lind, Folke; Jansson, Karl-Åke; Hajek, Michal; Smart, David; Fernandes, Tiago; Miller, Russell; Myles, Paul; Cameron, Peter
Abstract : Introduction: Open fractures with significant soft tissue injury are associated with high rates of complications, such as non-union, infection, chronic pain and disability. Complications often require further inpatient care, and in many cases, multiple operations and prolonged rehabilitation. Use of hyperbaric oxygen therapy as an adjunct to standard orthopaedic trauma care has the potential to reduce the complications of musculoskeletal injury and thus improve outcomes. Two previous randomised trials have suggested some positive effect, but neither functional measures nor long-term outcomes were reported. Methods and analysis: An international, multicentre, randomised, open-label, clinical trial. Patients with trauma with an acute open fracture of the tibia with severe soft tissue injury (Gustilo grade 3) and high risk of injury-related complications were recruited from participating major trauma hospitals with hyperbaric facilities. Patients were enrolled with the expectation of commencing 12 sessions of hyperbaric oxygen therapy within 48 h of injury. The primary outcome measure is the incidence of acute complications of the open fracture wound at 14 days. Other short-term outcome measures include amputation, need for fasciotomy, time until wound closure, breakdown of closed wounds, time until definitive orthopaedic fixation, number of operative procedures, intensive care stay and hospital stay. Long-term follow-up will continue for 2 years postinjury. Ethics and dissemination: Ethics approval was given by The Alfred Health Human Ethics Committee (206/04) and the Monash University Human Research Ethics Committee (CF07/4208). Approval was also obtained from the institutional research ethics committee at each participating site. This study will make a significant contribution to the trauma literature and should answer the question of whether hyperbaric oxygen therapy can significantly improve outcomes in severe lower limb trauma. Collective study results will be published in international journals and presented at relevant conferences. Trial registration number: Clinicaltrials.gov: NCT00264511 ; Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12607000559415.